Fluvial influence on the biochemical composition of particulate organic matter in the Laptev and Western East Siberian seas during 2015. (March 2020) - Ahn, So Hyun; Kim, KwanWoo; Jo, Naeun; Kang, Jae Joong; Lee, Jae Hyung; Whitledge, Terry E.; Stockwell, Dean A.; Lee, Ho Won; Lee, Sang Heon
Abstract: Here, we investigated the elemental (C/N ratio) and isotopic signatures (δ 13 C) and major biomolecules (carbohydrates, proteins, and lipids) and their relative abundance (i.e., the biochemical composition) in particulate organic matter (POM) to assess their origin and fate in the Laptev and western East Siberian seas during late summer/fall of 2015. In addition, we compared our results with the summer data of 2013 collected from Laptev and northwestern East Siberian seas. In accordance with the observed hydrological structure (i.e., a northward, warmer, diluted freshwater plume than previously observed in 2013), the more depleted δ 13 C (−28.2 ± 0.9‰) and higher C/N ratio (10.8 ± 2.0) than those of 2013 signalled that fluvially released terrestrial organic carbon (TerrOC) was the main source of the POM, unlike in 2013, when phytoplankton was the dominant source (δ 13 C = −24.9 ± 1.0‰, C/N ratio = 7.6 ± 2.4; Ahn et al., 2019). During the offshore transport of heterogeneous TerrOC, carbohydrates seem to be the primary contributor to the bulk POM as a result of selective degradation and hydrodynamic sorting. Despite the TerrOC-dominated system in 2015, some marine influence was also found. The estimated phytoplankton biomass was low and comparable among the study sites. In addition, the presence of resting spores and high ammonium concentrations within the water column may suggest senescent and, to some extent, degrading conditions of the resident phytoplankton. In this regard, carbohydrate concentrations and freshwater content were significantly correlated (r = 0.79, p < 0.01), suggesting that carbohydrates are useful inferences of freshwater within overall study sites, at least when the marine influence is similar or low. Highlights: Major biomolecules of POM were assessed for their origin and fate in the Laptev and western East Siberian seas. Carbohydrates was the primary contributor of POM during the offshore transport of heterogeneous terrestrial organic matter. Carbohydrates are useful inferences of fluvial released terrestrial input when the marine influence is similar or low .